An Empirical Juxtapose of the Effects of Self‐image on Entrepreneurial Career along the Spectrum of Nascent to Actual Entrepreneurs. Issue 4 (14th August 2018) - Salavou, Helen; Lioukas, Spyros
Abstract : This empirical study extends beyond efforts to contrast entrepreneurs with non‐entrepreneurs and elucidates comparisons among entrepreneurs . Specifically, it investigates capability and vulnerability self‐images among three groups of entrepreneurs to understand differences in perceptions . Using a sample of 725 graduate young entrepreneurs, multinomial logistic regression shows that low‐intention nascent, high‐intention nascent and actual entrepreneurs perceive their potential and fears differently . The evidence shows that nascent, compared to actual entrepreneurs have faith in most of their entrepreneurial abilities . In contrast, nascent are sensing more fears while experiencing the entrepreneurial process . In addition, high relative to low‐intention nascent entrepreneurs have higher creativity, higher networking skills and lower fear of failure . The discussion regarding why entrepreneurs do not constitute a homogenous population has important implications for both theory and practice .